FLORAE MALESIANAE PRAECURSORES XIII*Notes on Malaysian and some S. E. Asian Cyperaeeae IV* - KERN, J. H. (REINWARDTIA, 1956)
The difficulties encountered in this group could not be solved by the application of this key to the numerous specimens I could study. In the type specimen of Scirpus pakapakensis Stapf from Borneo, Mt. Kinabalu, the stems are not trigonous. Although in Thwaites CP306 (type collection of Scirpus subcapitatus) the mucros of the leaf-sheaths and of the outermost glume are practically smooth, they are scaberulous in several Indian specimens otherwise quite agreeing with the type collection. In some specimens from Mt. Kinabalu the stems are slightly scaberulous at the top; for the rest they agree very well with the type of Scirpus clarkei Stapf.